1985
DOI: 10.1111/j.1475-1313.1985.tb00653.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Illumination and Foveal Fusion Lock on Clinical Fixation Disparity Measurements With the Sheedy Disparometer

Abstract: The Sheedy Disparometer is a clinical instrument designed to measure fixation disparity and hence determine forced vergence--fixation disparity curves. The target design includes a central 1.5 degrees fusion-free area. The effect of introducing a central fixation target to the instrument is investigated along with the influence of ambient illumination level on fixation disparity. All curve parameters, i.e. curve type, slope, X- and Y-intercepts were found to significantly alter with the introduction of a fovea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 16 publications
3
10
3
Order By: Relevance
“…These results are consistent with the results of Yekta et al (1989) that amount of divergent y-intercept and base-in x-intercept increases with the lack of foveal lock. Also, our results are in concordance with findings of Brautaset & Jennings (2006), Wildsoet & Cameron (1985) and Debysingh et al (1986), who reported that FDC parameters with devices that have a foveal lock are more stable, and the x-intercept has a lower range. According to our findings, the standard deviation of the y-intercept and the x-intercept with the Wesson FD card were higher than the modified Mallett unit.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…These results are consistent with the results of Yekta et al (1989) that amount of divergent y-intercept and base-in x-intercept increases with the lack of foveal lock. Also, our results are in concordance with findings of Brautaset & Jennings (2006), Wildsoet & Cameron (1985) and Debysingh et al (1986), who reported that FDC parameters with devices that have a foveal lock are more stable, and the x-intercept has a lower range. According to our findings, the standard deviation of the y-intercept and the x-intercept with the Wesson FD card were higher than the modified Mallett unit.…”
Section: Discussionsupporting
confidence: 95%
“…In the studies of Ogle et al (1976), Sheedy & Saladin (1978), Wick (1985), Wildsoet & Cameron (1985), and Yekta et al (1989), the most prevalent curve type was type I, which is similar to our results.…”
Section: Strabismussupporting
confidence: 94%
“…In the studies of Ogle et al(13) Sheedy and Saladin, (7) Wick (8), Wildsoet and Cameron (28) and Yekta et al(17) the most prevalent curve type was type I, which is similar to our results. The previous studies reported that curve type is an important indicator of decompensated heterophoria, (7, 13) with curve type I as a normal curve and other curve types being more common in symptomatic subjects.…”
Section: Discussionsupporting
confidence: 91%
“…, 1949). The lack of a central fusion lock destabilises (Wildsoet and Cameron, 1985) and increases (Brownlee and Goss, 1988) fixation disparity and under these unnatural conditions fixation disparity is therefore a less useful indicator of visual stress (Evans, 2002).…”
Section: Introductionmentioning
confidence: 99%